Change in life expectancy with type 2 diabetes: a study using claims data from lower Saxony, Germany. Issue 1 (December 2017) - Muschik, Denise; Tetzlaff, Juliane; Lange, Karin; Epping, Jelena; Eberhard, Sveja; Geyer, Siegfried
Abstract Background This study estimates life expectancy with and without type 2 diabetes for individuals in Lower Saxony, Germany in order to detect a trend in population health. Methods Morbidity and mortality data derived from German administrative claims data (statutory health insurance, AOK Niedersachsen, N = 2, 900, 065) were used covering 10 years from 2005 to 2014. Life table analysis was applied for calculating life expectancy, life expectancy free of type 2 diabetes, life expectancy with type 2 diabetes, and the proportion of life expectancy free of diabetes to total life expectancy using the Sullivan method. Results The total life expectancy increase is stronger in men than in women: At the age of 20, total life expectancy was 55.0 years in 2005 and 56.3 years in 2014 for men, whereas it was 61.7 years in 2005 and 62.5 years in 2014 for women. Decreases in life expectancy without type 2 diabetes were more pronounced in women than in men. Accordingly, life expectancy with type 2 diabetes increased in both women and in men. The proportion of life expectancy without diabetes to total life expectancy decreased, indicating a similar development in both. For example, at the age of 60, the proportion of life expectancy without diabetes to total life expectancy decreased from 0.75 in 2005 to 0.66 in 2014 for men, while it decreased from 0.77 in 2005 to 0.70 in 2014 for women. Conclusions Against the background of increasing total life expectancy, the time spent in morbidity increased for the case of type 2 diabetes in Lower Saxony, Germany.